Suveræne livsytringer og kredsende tanker og følelser – en kritisk begrebsudvikling - Rabjerg, Bjørn (Dansk Teologisk Tidsskrift, 2014)
The absolute ontological difference between sovereign expressions of life and encircling thoughts and emotions in Løgstrup’s ethics and metaphysics reflects a fundamental distinction between that which is given (and thus not constituted by the self) and that which we ourselves must accept responsibility for. This ontological difference plays a central part through Løgstrup’s authorship from the 1930’s and until the formation of the concepts in the 1960’s, and beyond. As a consequence it is suggested that the term ‘encircling expressions of life’ must be abandoned, as it blurs this ontological difference and implies that man is not responsible for his own resentment and egotism.